Bilateral activation of glial cells and cellular distribution of the chemokine CCL2 and its receptor CCR2 in the trigeminal subnucleus caudalis of trigeminal neuropathic pain model - Kubíčková, Lucie; Klusáková, Ilona; Dubový, Petr (Histochemistry and cell biology, 2020)
Glial cells activated by peripheral nerve injury contribute to the induction and maintenance of neuropathic pain by releasing neuromodulating cytokines and chemokines. We investigated the activation of microglia and astrocytes as well as the cellular distribution of the chemokine CCL2 and its receptor CCR2 in the trigeminal subnucleus caudalis (TSC) ipsilateral and contralateral to infraorbital nerve ligature (IONL). The left infraorbital nerve was ligated under aseptic conditions, and sham controls were operated without nerve ligature. Tactile hypersensitivity was significantly increased bilaterally in vibrissal pads of both sham- and IONL-operated animals from day 1 to 7 and tended to normalize in sham controls surviving for 14 days. Activated microglial cells significantly increased bilaterally in the TSC of both sham- and IONL-operated animals with a marked but gradual increase in the ipsilateral TSC from 1 to 7 days followed by a decrease by day 14. In contrast, robust activation of astrocytes was found bilaterally in the TSC of IONL-operated rats from 3 to 14 days with a transient activation in the ipsilateral TSC of sham-operated animals. Cellular distribution of CCL2 varied with survival time. CCL2 immunofluorescence was detected in neurons within 3 days and in astrocytes at later time points. In contrast, CCR2 was found only in astrocytes at all time points with CCR2 intensity being dominant in the ipsilateral TSC. In summary, our results reveal bilateral activation of microglial cells and astrocytes as well as changes in the cellular distribution of CCL2 and its receptor CCR2 in the TSC during the development and maintenance of orofacial neuropathic pain.
Keywords: neuralgie; Male; Rats, Wistar; Microglia; chemokin CCL2; Animals; potkani Wistar; Substantia Gelatinosa; Neuroglia; mužské pohlaví; Neuralgia; substantia gelatinosa; krysa rodu Rattus; neuroglie; modely nemocí na zvířatech; Rats; Unilateral nerve injury; Infraorbital nerve; Receptors, CCR2; zvířata; receptory CCR2; Chemokine CCL2; Disease Models, Animal; Astrocytes